Diagnostic Accuracy of Ultrasonography in Diagnosis of Metatarsal Bone Fracture; a Cross Sectional Study - Mohsen Ebrahimi; Seyed Reza Habibzadeh; Syyed Reza Ahmadi; Samaneh Khajeh Nasiri; Mohammad Majid Kaveh; Mahdi Foroughian (Archives of Academic Emergency Medicine)
Introduction: Metatarsus is one of the most common sites in the sole of foot bones fractures. The aim of this study was to determine the diagnostic accuracy of ultrasound in diagnosis of metatarsal bone fractures following foot trauma. Methods: This cross-sectional study was carried out on patients with blunt foot trauma admitted to emergency department of a hospital in Mashhad, Iran from January to September 2016. All patients were evaluated with bedside ultrasound for the presence of first to fifth metatarsal fractures and screening performance characteristics of ultrasonography in detection of metatarsal fractures were calculated considering foot radiography as the reference test. Results: The study was conducted on 102 patients with a mean age of 35.14Â±14.32 years (56.8% male). The most common signs of trauma in physical examination were pain and tenderness (100%), swelling (96.1%), ecchymosis (14.7%) and deformity (1.9%). Sensitivity, specificity, and positive and negative likelihood ratio of ultrasonography in detection of metatarsal bone fracture were 96.7% (95% CI: 0.83-0.99), 84.5% (95% CI: 0.73-0.92), 73.1% (95% CI: 0.57-0.85), and 98.3% (95% CI: 0.91-0.99), respectively. The overall accuracy of ultrasonography was 0.906 (95% CI: 0.844 â€“ 0.969) based on area under the receiver operating characteristic (ROC) curve. Conclusion: Considering the excellent diagnostic accuracy, ultrasonography can be used as an alternative means in diagnosis of metatarsal bone fractures.